2019
DOI: 10.3390/cancers11101450
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Models to Define the Genetic Predisposition to Liver Cancer

Abstract: Hepatocellular carcinoma (HCC) is a frequent human cancer and the most frequent liver tumor. The study of genetic mechanisms of the inherited predisposition to HCC, implicating gene–gene and gene–environment interaction, led to the discovery of multiple gene loci regulating the growth and multiplicity of liver preneoplastic and neoplastic lesions, thus uncovering the action of multiple genes and epistatic interactions in the regulation of the individual susceptibility to HCC. The comparative evaluation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 134 publications
0
13
0
Order By: Relevance
“…Previous study of the genetic mechanisms of the inherited predisposition to HCC, based on the comparative evaluation of the molecular pathways involved in HCC developing in rat strains differently predisposed to HCC, have shown that the genes responsible for the susceptibility to HCC control the amplification and/or overexpression of c- Myc , the expression of cell cycle regulatory genes, the activity of Ras/Erk and Akt/mTor , the methionine cycle, and DNA repair pathways [ 84 ]. The activation of oncogenes or the mutation of oncosuppressor genes, including p53, may be responsible of different deregulations leading to glycolytic metabolism and to the inhibition of the respiratory enzymes including cytochrome c oxidase.…”
Section: The Genetic Susceptibility To Cancermentioning
confidence: 99%
“…Previous study of the genetic mechanisms of the inherited predisposition to HCC, based on the comparative evaluation of the molecular pathways involved in HCC developing in rat strains differently predisposed to HCC, have shown that the genes responsible for the susceptibility to HCC control the amplification and/or overexpression of c- Myc , the expression of cell cycle regulatory genes, the activity of Ras/Erk and Akt/mTor , the methionine cycle, and DNA repair pathways [ 84 ]. The activation of oncogenes or the mutation of oncosuppressor genes, including p53, may be responsible of different deregulations leading to glycolytic metabolism and to the inhibition of the respiratory enzymes including cytochrome c oxidase.…”
Section: The Genetic Susceptibility To Cancermentioning
confidence: 99%
“…Transgenic species-The use of transgenic species or even mice with a humanized liver [99] could aid in mechanistic studies or down-stream analysis of (specific) chronic liver disease in a more human-like setting. Although several genetically modified species are available, e.g., for NAFLD [100] or liver cancer [101], only a few PCLS research papers make use of transgenic species. We recommend the use of transgenic species for PCLS research, as this would improve the progression in chronic liver disease research.…”
Section: Liver Diseasementioning
confidence: 99%
“…Genetically engineered mouse models (GEMMs), cell line-derived xenograft (CDX) or patient-derived xenograft (PDX) models, and humanized mouse models (HMMs) have their own benefits and are commonly employed in cancer research [19,20,21,22,23,24,25,26,27,28,29,30]. Nevertheless, several issues in the development of animal models for cancer research have been encountered, such as different susceptibility of various mouse and rat strains to cancers, genetic diversions and technical variations in the animals, and polygenic predisposition in different strains controlled by multiple genetic loci [31,32,33,34,35,36,37,38]. Based on these and other limitations, currently used animal models might result in an inaccurate recapitulation of tumor development, leading to discrepancies between the outputs of preclinical research and clinical trials for development of cancer treatment [39,40,41].…”
Section: Discussionmentioning
confidence: 99%